Russian Federation Systematic Country Diagnostic : Pathways to Inclusive Growth - World Bank (World Bank, Moscow, 2017)
Russia is a country of global importance and great internal diversity, making it challenging to undertake acoherent country growth diagnostic. The world’s largest transcontinental country spans eleven time zones in northern Eurasia. Russia is the main trading partner for many of its more than a dozen neighbors. It also is thehost of 11 million migrants who generate significant remittances for their home countries. As a growing upper middle-income economy, it plays an increasing role as a donor to low-income economies worldwide. Russia isthe ninth most populous country in the world with an admirable track-record in reducing poverty and boosting shared prosperity. Russia is unevenly populated and economic activity is dispersed, preventing the scale advantages of agglomeration. Altogether, these characteristics render undertaking this Systematic Country Diagnostic aboutRussia’s future development course challenging. The analysis identifies general causal chains related to Russia’sinterlinked development challenges and opportunities, but is often based on data only available at the national level. This diagnostic identifies two pathways where progress is critical for sustainable growth and an expansion of shared prosperity. The first pathway identified areas where new policies are necessary to achieve a recoveryin productivity, focusing on infrastructure and connectivity, the regulatory regime for businesses, constraints on innovation by firms, and skills development for individuals. The second pathway identified the main areas for policy reforms to further reduce vulnerability by deepening human capital gains and improving access to public services. The analysis identifies channels through which the labor market can again become a source of raising the incomes of the bottom 40 percent by improving health and education services and strengthening the poverty impact and sustainability of Russia’s social protection system. To achieve these goals, progress isessential in three requisites: fiscal sustainability, governance, and management of natural resources.